Pengaruh Motivasi dan Disiplin terhadap Kinerja Pegawai Pemerintah Aparatur Sipil Negara pada Sekretariat Daerah Muaro Jambi - Agustin, Dwi Aulia (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to analyze the effect of motivation and work discipline on employee performance using multiple linear regression methods. This research aims to determine the extent of the influence of the variables of motivation and work discipline on employee performance in an institution or organization. The research methodology used is quantitative descriptive analysis method. Muaro Jambi Regional Secretariat is part of the Jambi Province Region, formed based on Law Number 54 of 1999 as an expansion of Batanghari Regency. Address of the Regional Secretariat of Muaro Jambi: Bukit Baling, Sekernan Sub-district, Muaro Jambi Regency, Jambi Province, 36381.Muaro Jambi Regency originally consisted of 7 sub-districts and 120 villages bordered by East Tanjung Jabung and West Tanjung Jabung Regencies to the north and South Sumatra Province to the west. Now, Muaro Jambi Regency has 11 sub-districts, 5 villages, and 150 villages. The sample used in this study amounted to 53 employees. The data collected were analyzed using multiple linear regression to see the relationship between the independent variables (motivation and work discipline) and the dependent variable (employee performance). This study also used ANOVA test to test the significance of the regression model. Based on the information obtained, it is known that the average employee performance, motivation, and work discipline are 43.79, 43.08, and 41.11, respectively, with varying standard deviations. The regression analysis results show a very strong relationship between the independent variables and the dependent variable, with an R value of 0.955 and an R² value of 0.911. The ANOVA test results indicate that the regression model used is significant, with an F value of 288.313. The regression coefficients for the motivation variable are 0.319 and for the work discipline variable are 0.326, which indicates that both have a positive and significant effect on employee performance, with a significance value of 0.000. From the results of this study, it can be concluded that motivation and work discipline have a significant impact on employee performance. These findings support the hypothesis that increasing motivation and work discipline will improve employee performance. The practical implications of this research highlight the importance of organizations enhancing motivation and work discipline through various incentives and supportive policies to improve overall employee performance. Keywords: Motivation, Work Discipline, Performance